Hubungan Pengetahuan Tentang Makanan Bergizi Seimbang Dengan Sikap Peserta Didik - Achya, Feny Fadillah; Taiyeb, Mushawwir; Pagarra, Halifah (Universitas Negeri Makassar, 2021)
Abstract. This research was conducted at SMA Negeri in Biringkanaya District, Makassar City, including SMAN 18 Makassar, SMAN 7 Makassar, SMAN 22 Makassar. Knowledge of balanced nutrition is part of the community's reference to nutrition, including adolescents, so this is an effort to increase adolescent knowledge with the hope of changing unbalanced nutritional behavior. This knowledge will raise awareness, and eventually will cause people to behave in accordance with the knowledge they have. This study aims to determine the relationship between knowledge about balanced nutrition and attitudes towards balanced nutrition. The method used in this study is a descriptive method with a survey method, using tests and questionnaires. The results of the research knowledge obtained 5.9% in the good category, 11.9% sufficient category, 82.0% less category. While the attitude of 29.8% in the sufficient category, 7.4% less, and 62.4% good. There is a relationship between the knowledge and attitudes of SMA Negeri students in Biringkanaya District, Makassar City, which is categorized as weak. It is necessary to provide education about Balanced Nutrition Knowledge for students.Keywords: Knowledge of nutrition, attitude towards nutrition